Wrap it up: myelination of transplanted neurons for repair - Martínez-Reza, María Fernanda; Götz, Magdalena (Frontiers in Cellular Neuroscience, 2025)
Degeneration or damage of neuronal circuits in the central nervous system can lead to an irreversible loss of neurons and function in the affected brain region. Neuronal transplantation is a promising therapeutic approach consisting of introducing healthy cells into the damaged or diseased regions to restore lost circuits. To achieve successful neuronal transplantation, proper integration of the graft in the host circuitry is necessary. This includes the restoration of connectivity as well as the recapitulation of the physiological characteristics of the lost endogenous neurons. An often-overlooked aspect to assess the integration of transplanted neurons is the acquisition of cell-extrinsic features, such as myelination. This review explores the interaction between transplanted cells and endogenous oligodendroglia, the evidence of myelination in different neuronal transplantation models, and the checkpoints that can influence graft myelination in the injured or diseased brain. Additionally, it discusses how appropriate myelin ensheathment could help overcome some challenges faced in the field of neuronal replacement.